Respostas

2014-07-11T02:05:40-03:00
182) 2² - (-3)² - [4x(-1)]² =
2² - (-3)² - [-4]² =
2² - (-3)² - [16] =
4 - 9 - 16 =
-21

183) - {-12 - (-8)² - [-2+5x(-3 +9)]} =
- {-12 - (-8)² - [-2+5x(6)]} =
- {-12 - (-8)² - [-2+30]} =
- {-12 - (-8)² - [28]} =
- {-12 - (-8)² - 28} =
- {-12 - 64 - 28} =
- {-104} =
104

184) parece que faltou algo

185) -5² + (-3) x (-1 + 7) - [3 -5 x(-1 +2)] =
-5² + (-3) x (-1 + 7) - [3 -5 x (1)] =
-5² + (-3) x (-1 + 7) - [-2 x 1] =
-5² + (-3) x (-1 + 7) - [-2 ] =
-5² + (-3) x (-1 + 7) +2 =
-5² + (-3) x (6) +2 =
-5² -18 +2 =
-25-18+2 =
-25-16 =
-41

186) Parece que faltou algo

187) (8 x 2 - 10) + (18 - 4 x 4) =
(16 - 10) + (18 - 16) = 
6 + 2 =
8

188) 80: (2 x 4 + 2) - 7 =  
80: (8 + 2) - 7 =  
80: (10) - 7 =  
8 - 7 =
1

189) (20:10 + 10) : (5 x 2 + 2) = 
(2 + 10) : (10+ 2) = 
12:12 =
1

190) 100 - {2 x [18 - (4 x 2 - 6)]} = 
100 - {2 x [18 - (8 - 6)]} =
 100 - {2 x [18 - (2)]} =
100 - {2 x [18 - 2]} =
100 - {2 x [16]} =
100 - {2 x 16} =
100 - {32} =
100 - 32 =
68

191) 5³ - 2^4 x 4 =
 125 - 16x4 =
125 - 64 =
61

192) (5x 2- 9)³ +( 2^4 - 8x2) =
(10 - 9)³ + (16 - 16) =
1 + 0 =
1

193) (5 + 2 - 3)² : 8 + (3² - 2 x 3) =
(4)² : 8 + (9 - 6) =
16 : 8 + 3 =
2 + 3 =
5

194) 5³ - [ 2 + (5 - 3+2)²] =
5³ - [ 2 + (4)²] =
5³ - [ 2 + 16] =
5³ - [ 18] = 
125 - 18 =  
107

195) (4 + 2)² :4 - [20 - (1 +3)² =
(4 + 2)² :4 - [20 - ( 4 )²]=
(4 + 2)² :4 - [20 - 16] =
(4 + 2)² :4 - [4]=
(4 + 2)² :4 - 4=
(6)² :4 - 4 =
36 :4 - 4 =
9 - 4 =
5

Abraços.